Direct quantification of 3' terminal 2'-O-methylation of small RNAs by RT-qPCR. - Wang, N.; Qu, S.; Sun, W.; Zeng, Z.; Liang, H.; Zhang, C.Y.; Chen, X.; Zen, K. (RNA (New York, N.Y.), 2018)
Modification of nucleotides significantly increases the diversity of functional nucleic acids. As one of the most common modifications of RNAs, methylation of the 2'-hydroxyl-group of ribonucleotides (2'-O-methylation) has been found in various RNAs in eukaryotes. However, due to the lack of an efficient method for quantifying small RNA 3' terminal 2'-O-methylation, it is difficult to monitor the dynamic change of 3' terminal 2'-O-methylation during various biological processes. Capitalizing on the finding that 3' terminal RNA 2'-O-methylation can inhibit the activity of poly(A) polymerase, an enzyme that can add the poly(A)-tail to RNA, we develop a method by which the 2'-O-methylation level of small RNAs, such as microRNAs (miRNAs) and Piwi-interacting RNAs (piRNAs), can be directly quantified based on the poly(A)-tailed RT-qPCR technique. With this method, we successfully determine the 2'-O-methylation level of miRNAs in Arabidopsis thaliana and mouse lung tissue, piRNA in human seminal plasma, and monitor the alteration of miRNA 2'-O-methylation in Drosophila Schneider 2 cells after knockdown of Drosophila methyltransferase protein Hua enhancer 1 (DmHen-1).